Macrophages are critical to the maintenance of IL-13-dependent lung inflammation and fibrosis - Borthwick, Lee A. (Mucosal Immunol, 2015)
The roles of macrophages in type 2-driven inflammation and fibrosis remain unclear. Here, using CD11b-Diphtheria Toxin Receptor (DTR) transgenic mice and three models of IL-13-dependent inflammation, fibrosis, and immunity, we show that CD11b(+) F4/80(+) Ly6C+ macrophages are required for the maintenance of type-2 immunity within affected tissues but not secondary lymphoid organs. Direct depletion of macrophages during the maintenance or resolution phases of secondary S. mansoni egg-induced granuloma formation caused a profound decrease in inflammation, fibrosis, and type-2 gene expression. Additional studies with CD11c-DTR and CD11b/CD11c-DTR double transgenic mice suggested that macrophages but not dendritic cells were critical. Mechanistically, macrophage depletion impaired effector CD4(+) Th2 cell homing and activation within the inflamed lung. Depletion of CD11b(+) F4/80(+) Ly6C(+) macrophages similarly reduced house dust mite-induced allergic lung inflammation and suppressed IL-13-dependent immunity to the nematode parasite Nippostrongylus brasiliensis. Consequently, therapeutic strategies targeting macrophages offer a novel approach to ameliorate established type-2 inflammatory diseases.